As competências do bibliotecário na Sociedade da Informação: o ponto de vista do profissional - Karine de Souza Resende (2021)
One of the characteristics of the Information Society is the intense use of information technologies and knowledge. In this reality, new competencies are required of professionals such as the librarian, who needs to acquire and apply knowledge, skills and abilities to respond to these demands in a scenario of intense technological and social changes. The general objective of the research was to identify the librarian’s competencies for their professional performance in this new society. The professional is constantly challenged to face the transformations and ensure appropriate skills for work in an environment marked by continuous changes. Thus, characterizing the competencies of librarians in the context of the contemporaneity of the Information Society is the problem of this research, which is justified by the relevance of the theme for the area of Information Science and society, mainly due to the approach to cooperate for the performance in the labor market and continuous education of the librarian. The descriptive research, with a quantitative approach, used for data collection the bibliographic research and a questionnaire and, for data analysis, descriptive statistics and factor analysis. This model was built with 44 statements that represent competencies for the professional performance of the librarian. The competencies they were divided into seven categories: Research and Evaluation, Continuing Education and Professional Development, Administration and Supervision, Trends and Fundamentals of the Profession, Technology, Reference services and Information and Personal Qualities. The questionnaire was applied to 94 librarians of the city of Belo Horizonte, Brazil. Descriptive statistics supported data analysis with the calculation of frequencies, means and standard deviations. With the software SPSS Statistics factor analysis was used to examine the relationships among the competencies of the model. The bibliographic research resulted in the identification of models consolidated in the literature and enabled the adaptation of a model of competencies model to support the preparation of the questionnaire. The main results of the research indicate that ten competencies most valued, in the opinion of professionals, are in the categories Personal qualities, Research and evaluation, Continuing Education and Professional Development, Administration and Supervision and Trends and Fundamentals of the Profession. On the other hand, the ten least important competencies, considering the averages, are almost all in the category Technology, Research and Evaluation and Personal Qualities. Moreover, in factor analysis, factor 1 synthesized the majority of competencies of the proposed model, which meant the grouping of 34 competencies in this group. All categories were contemplated with at least some competency in this factor. It is believed that the results of the study represent a picture consistent with the current reality of the work of librarians and that the research contributed to the area of knowledge related to the study of professional competency, because the results obtained allow the recognition of evidence necessary for their professional performance.